Bird communities and vegetation composition in natural and semi-natural forests of megalopolis: correlations and comparisons of diversity indices (Kyiv city, Ukraine) - Blinkova, Olena; Shupova, Tetyana (Ekológia Bratislava, 2018)
Assessment of correlations and comparisons of diversity indices between birds communities and vegetation composition of the forest ecosystem is an important subject of synecological research to identify the intensity of human impact on the flora and fauna in megalopolis. Urban recreation is one of the major causes of violation of the structural and functional integrity of the forest ecosystem. Studies on avian complex and phytocoenosis have focused on the impact of urban recreation on the soil surface, compositions of trees, shrub and herbaceous layers and species, trophic and ecological compositions of nesting-birds and feeding-birds communities. This article compares the measurement of the diversity of bird communities and forestry vegetation (diversity indices, dominance indices, evenness indices) in the natural and semi-natural forests of the Kyiv city on a gradient of recreational transformation. The stands formed consist of L., L., L., L., Huds., L. and L. The floristic list comprised 65 grass species. A total of 49 species of avifauna were found, including 44 species that were protected by the Bern, Bonn and Washington Conventions. There were significant correlations between vertical and horizontal heterogeneities of tree distribution and abundance, species richness and nesting density of birds. The interrelationship between species diversity of birds and floristic richness was also confirmed.